Fostering online social capital through peer-support. (2015) - Fetter, Sibren; Vegt, Wim Van der; Sloep, Peter
Fostering social capital in online learning networks is essential for networked learning. Peer-support through so-called ad hoc transient groups (AHTGs) can help to socialise the network. A user-centric qualitative experiment was carried out to gauge the effect of AHTGs on social capital. Participants, who had access to AHTGs and a forum, were asked to fill in questionnaires and to participate in email interviews. The results confirm the hypothesis that participants believe the use of AHTGs will positively affect all aspects of social capital, except strengthening existing relationships. The participants viewed the AHTGs and the forum that was provided as sufficiently distinct from each other that these interaction environments could coexist and be mutually beneficial.